Balanced scorecard model based on quality management system requirements: evidence from the Iranian ferro industry - Asgari, Nasrin; Avakh Darestani, Soroush; Ismail, Md Yusof; Ahmadpour, Leila (Inderscience Publishers, 2023)
Performance evaluation is to ensure performance consistency with plans and compare actual performance with targets that have already been set. BSC is one of the convenient and efficient means for evaluating performance as well as measuring understanding of organization’s strategies and goals. The purpose of this study is to provide a model for assessing key indices of BSC in a QMS. As importance of quality is growing in today's world, integrity of balanced scorecard and quality management system can create a significant combination approach. Accordingly, tree methods including Fuzzy DEMATEL, Fuzzy ANP and Fuzzy VIKOR with the theme of multi criteria optimization were integrated by the authors and then, solutions were compromised. Furthermore, this novel hybrid methodology was applied in developing an assessment model. Results of the proposed model implemented in a Ferro Complex industry and show that production and quality control departments are known as optimal units with high performance. R&D, financial, administrative and marketing departments are ranked third to sixth respectively.